TINJAUAN TENTANG KESEIMBANGAN PERAN PENEGAK HUKUM (POLISI) DAN PERLINDUNGAN HAK ASASI MANUSIA (HAM) - Ferdricka Nggeboe (Jurnal LEX SPECIALIS, 2010)
The principle of law country is started with the right of equality before the law. The meaning of balance is meant that police doesn’t need to cut it’s job and function. However positive control is needed on order to execute law enforcement duty by paying attention to human rights especially to a suspected or a defendant. The function of positive control is better to be done in the circle of POLRI organization it self by keeping the objectivity and professionalism improvement in every police individuals. Key Note : Law enforcement in human rigths